The Inner Kalacakratantra: A Buddhist Tantric View of the Individual. Vesna A. Wallace. - Tlalim, Ronit Yoeli (Buddhist Studies Review, 2002)
The Inner Kalacakratantra: A Buddhist Tantric View of the Individual. Vesna A. Wallace. Oxford University Press, Oxford 2001. x, 273 pp. £45.00. ISBN 0-19-512211-9.